SOCIO-PSYCHOLOGICAL FEATURES OF PULMONARY MDR/XDR TB MALE PATIENTS (COMPARISON WITH A RANDOMIZED SAMPLE OF HEALTHY MEN) - Vartan Tarasovich Chubaryan; Galina Ivanovna Saenko; Igor Yuryevich Khudonogov; Ekaterina Vladimirovna Modebadze (Siberian journal of life sciences and agriculture, 2019)
Rationale. studies of the clinical efficacy of various medical technologies used in the emergence of MDR/XDR Mycobacterium Tuberculosis (MBT) have been conducted quite often in recent decades. However, to a large extent, they are focused on the safety of new treatment regimens, on molecular genetic diagnostic methods, on the development of technological platforms for creating innovative anti-TB drugs, etc. Less is known about the socio-psychological, medico-social and economic background of MDR appearance. Objective. we sought to identify the group socio-psychological characteristics of MDR/XDR TB male patients compared with a randomized sample of healthy men. Next, we examined the socio-economic predictors of MDR/XDR appearance. Methods. we used historical, sociological and statistical methods: t-test, logistic regression, growth rate relative to the level of one of the groups, taken as 100%. To analyze the data, a cohort of adult RCPC patients was formed – 42 men with MDR or XDR MBT – and a control group – 38 adult men, residents of Rostov-on-Don and the Rostov Region. The MDR/XDR MBT Integrative Predictor was calculated using the loss-acquisition index (LAI). Results. logistic regression model of MDR (XDR) MBT, based on sociological data, included the following properties of patients, significantly distinguishing them from healthy participants in the survey: sex – men are most vulnerable to MBT with MDR (XDR); when comparing same-sex groups, the following indicators were distinguished: “I can’t get along with people” – (OR = 6.33, 95%, CI = 1.35, 29.7); “Order in our country can only be achieved through brute force and cruel punishment (I am for the death penalty)” – (OR = 10.86, 95%, CI = 1.35, 87.49); “I remember about my health only when any symptoms appear” – (OR = 3.17, 95%, CI = 1.29, 7.79); “I am fully informed of all risks to my health from doctors” – (OR = 2.35, 95%, CI = 1.00, 5.51); “Doctors have outlined a specific plan to reduce the risks to my health” – (OR = 3.92, 95%, CI = 1.46, 10.55); “I am actively opposing risk factors, but I am not achieved a positive result” – (OR = 8.14, 95%, CI = 1.77, 37.43); “I have bad habits, but I consult with doctors about my current condition” – (OR = 5.88, 95%, CI = 1.88, 18.4); “I have no strategy - I live how I live” – (OR = 3.02, 95%, CI = 1.10, 8.30); “I do not have concrete plans, I can’t imagine my future clearly” – (OR = 10.00, 95%, CI = 2.1, 47.51) Conclusion. the data obtained indicate that patients of the 1st group show high aggressiveness, they are characterized by loneliness, infantilism, low social adaptation which deprives them of the opportunity to lead a socially and economically productive life (the group loss-acquisition index was in the negative values zone). The obtained data were used to develop an information and cognitive program to support the main treatment process.